CONFLICT PREDICTION AND RESOLUTION WITH TWO DIMENSIONAL GEOMETRIC OPTIMIZATION ON AIR TRAFFIC CONTROLLER SIMULATOR - ANDRIANA (NIM: 23207147), DIAN
One of air traffic controller (ATC) tasks is to maintain minimum separation between aircrafts. This task can be helped by air traffic management automation softwares. The software could be a decision support system which predict conflict and advise resolution to change aircraft heading to be able to avoid conflict. The research aim is to design and implement software that predict conflict and advise resolution through heading changes of the aircraft in the ATC simulator. Functional requirement testing has been done to check capabilities of conflict detection, prediction, and resolution, and also turn-back point to flight-plan route. Nonfunctional aspects such as speed uncertainties and heading change delays have been added to the aircraft movement simultaneously during testing processes. System performance improvement has been discussed to increase resolution optimality.